CRISPR/Cas9-engineered inducible gametocyte producer lines as a valuable tool for Plasmodium falciparum malaria transmission research - Sylwia D. Boltryk (Nature Portfolio, 2021)
During each replication cycle of P. falciparum in the human bloodstream, a small proportion of parasites commits to sexual development and differentiates into transmission-relevant gametocytes. Applying CRISPR-based genome editing, Boltryk et al. engineer P. falciparum lines with sexual commitment rates of 75% to promote future studies on gametocyte biology.